Curable silicone composition, silicone rubber cured product, wire coated with silicone rubber cured product, and method for producing the same
Patent Information
- Application Number
- JP2023139451
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明により、芯線密着防止性が改善されたシリコーンゴム硬化物を形成する硬化性シリコーン組成物、及び該シリコーン組成物を硬化させてなるシリコーンゴム硬化物で被覆された電線を提供することができる。
Smart Images

Figure 2025033613000001 
Figure 2025033613000002 
Figure 2025033613000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable silicone composition, and more specifically to an electrically insulating curable silicone composition for coating electric conductors such as electric wires (including power cables; the same applies hereinafter), and to a silicone rubber-coated electric wire coated with a cured silicone rubber formed from the silicone composition. [Background technology]
[0002] Silicone rubber is used as a wire coating material because it has excellent heat resistance, cold resistance, and weather resistance, as well as excellent electrical insulation resistance. However, this type of silicone rubber has a weakness in that it has lower mechanical strength than general organic rubber. For this reason, silicone rubber cured product coated electric wires are required to be reinforced by applying braiding such as glass braiding on the silicone rubber insulation layer (a layer made of silicone rubber, which is a cured product). In addition, various varnishes are used as bundling materials to bundle the braiding, but when the varnish is cured by heat treatment, the silicone rubber insulation layer and the electric wire, which is the core wire, are likely to adhere to each other. A similar phenomenon also occurs when silicone rubber cured product coated electric wires are subjected to secondary heat treatment to improve electrical properties, and this is an extremely important problem in processing. That is, silicone rubber cured product coated electric wires have a problem that they cause core adhesion during terminal processing such as soldering, causing the inconvenience of silicone rubber, which is a cured product, remaining on the core wire, which is an electrical conductor, making it impossible to process the terminals.
[0003] On the other hand, in order to prevent the above-mentioned core wire adhesion, Patent Document 1 (JP Patent Publication 62-26124) describes a silicone rubber composition containing a fatty acid or a fatty acid metal salt and zinc oxide powder. However, the silicone rubber composition was insufficient in preventing the core wire from sticking, especially at high temperatures.
[0004] On the other hand, Patent Document 2 (JP 2019-77735 A) describes a silicone composition for power cables that contains an organosilicon compound having a nitrogen-containing organic group and an unsaturated hydrocarbon group, and a compound selected from benzotriazole or its derivatives. The silicone composition has a small tensile permanent set, excellent mechanical strength such as tensile strength and tear strength, and excellent high-voltage electrical insulation properties, and has the effect of suppressing the progression of material destruction after the occurrence of erosion. However, there is no description of the core wire adhesion prevention property that is the issue of the present invention, and the effect cannot be expected.
[0005] On the other hand, Patent Document 3 (JP Patent Publication 2008-163122 A) and Patent Document 4 (JP Patent Publication 2006-056986 A) describe addition-curing silicone rubber compositions that can form silicone rubber molded bodies with small compression set without secondary heat treatment after primary curing containing a metal damage inhibitor. However, these compositions are limited to addition-curing types, and there is no mention or suggestion of the technical significance of using a specific metal oxide and a metal damage inhibitor in combination in a certain quantitative range, or of the core wire adhesion prevention properties. Furthermore, these documents do not describe or suggest anything about curable compositions containing organic peroxides. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 62-26124 [Patent Document 2] JP 2019-77735 A [Patent Document 3] JP 2008-163122 A [Patent Document 4] JP 2006-056986 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a curable silicone composition that forms a cured silicone rubber product that has good core wire adhesion prevention properties (also known as wire stripping properties), and an electric wire covered with the cured silicone rubber product obtained by curing the silicone composition. [Means for solving the problem]
[0008] As a result of extensive investigation, the present inventors have found that (A) 100 parts by mass of an organopolysiloxane having at least two alkenyl groups in one molecule, (B) BET specific surface area is 50m 2 / g or more: 5 to 100 parts by mass, (C) Metal damage inhibitor: 0.05 to 5 parts by mass (D) (D1) One or more metal oxides selected from titanium oxide and (D2) magnesium oxide: 0.1 to 10 parts by mass (E) One or more curing agents selected from (E1) an addition reaction curing agent and (E2) an organic peroxide: an amount necessary for curing the present composition The inventors have discovered that the above problems can be solved by a curable silicone composition containing the compound (C), and have arrived at the present invention. However, unless component (C) is used in combination with a specific component (D), the core wire adhesion prevention properties of the obtained silicone rubber cured product cannot be sufficiently improved.
[0009] In addition, in the composition, The component (C) is preferably one or more compounds selected from (C1) a diacylhydrazide compound and (C2) an aminotriazole compound; The component (D) preferably contains (D1) titanium oxide; The component (E) preferably contains an organic peroxide (E2); It is preferable that component (A) is a raw rubber-like organopolysiloxane having a Williams plasticity in the range of 100 to 800, as measured in accordance with the method specified in JIS K6249; It is preferable that the composition further contains (F) 0.05 to 50 parts by mass of a diorganopolysiloxane capped at both molecular chain terminals with silanol groups and having a viscosity at 25° C. of 1 to 1,000 mPa·s.
[0010] Furthermore, the above-mentioned problems are solved by a cured silicone rubber obtained by curing the curable silicone composition; an electric wire covered with a cured silicone rubber, which has a core wire covered with the cured silicone rubber; and a method for producing a cured silicone rubber covered electric wire, which includes the steps of applying the curable silicone composition onto a core wire and curing the composition. Effect of the Invention
[0011] The present invention can provide a curable silicone composition that forms a cured silicone rubber product with improved core wire adhesion prevention properties, and an electric wire covered with a cured silicone rubber product obtained by curing the silicone composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Curable Silicone Composition] The composition according to the present invention comprises (A) an organopolysiloxane having at least two alkenyl groups in one molecule, (B) an organopolysiloxane having a BET specific surface area of 50 m 2 The composition preferably contains a silica powder having a viscosity of at least 1000 μg / g, (C) a metal damage inhibitor, (D) one or more metal oxides selected from (D1) titanium oxide and (D2) magnesium oxide, and (E) one or more curing agents selected from (E1) an addition reaction curing agent and (E2) an organic peroxide in a specific quantitative range, and further contains (F) a diorganopolysiloxane capped with silanol groups at both molecular chain terminals and having a viscosity at 25°C of 1 to 1,000 mPa s. In addition, for practical purposes, the composition may further contain (G) a cure retarder and may contain other optional compounding ingredients. Each component and its quantitative range will be described below.
[0013] Component (A) is the main component of the composition and has one or more types of curing reactivity selected from addition curing reaction and peroxide curing reaction, specifically, it is an organopolysiloxane having at least two alkenyl groups in one molecule. The alkenyl group is preferably an alkenyl group bonded to a silicon atom, and examples of the alkenyl group include alkenyl groups having 2 to 12 carbon atoms such as vinyl group, allyl group, butenyl group, pentenyl group, hexenyl group, heptenyl group, octenyl group, nonenyl group, and decenyl group, and preferably vinyl group and hexenyl group. Examples of groups other than alkenyl groups that are bonded to silicon atoms in component (A) include alkyl groups having 1 to 12 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, and heptyl groups; aryl groups having 6 to 12 carbon atoms, such as phenyl, tolyl, and xylyl groups; aralkyl groups having 7 to 12 carbon atoms, such as benzyl and phenethyl groups; and fluoroalkyl groups having 3 to 12 carbon atoms, such as 3,3,3-trifluoropropyl, 4,4,4,3,3-pentafluorobutyl, 5,5,5,4,4,3,3-heptafluoropentyl, 6,6,6,5,5,4,4,3,3-nonafluorohexyl, and 7,7,7,6,6,5,5,4,4,3,3-undecafluoroheptyl groups, of which methyl, phenyl, and 3,3,3-trifluoropropyl groups are preferred. Furthermore, small amounts of hydroxyl groups or alkoxy groups such as methoxy groups and ethoxy groups may be bonded to silicon atoms in component (A) as long as the object of the present invention is not impaired.
[0014] The molecular structure of component (A) is not limited, and examples thereof include linear, branched, partially branched linear, and resinous. In particular, from the viewpoint of improving the core wire adhesion prevention properties of the silicone rubber cured product obtained by curing the composition according to the present invention, it is preferred that a part or all of component (A) is a raw rubber-like organopolysiloxane having a Williams plasticity in the range of 100 to 800, preferably 100 to 400, as measured according to the method specified in JIS K6249.
[0015] Examples of such component (A) include dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with silanol groups, and dimethylvinylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxane terminal-blocked dimethylsiloxane-methyl(3,3,3-trifluoropropyl)siloxane copolymer, terminal-blocked dimethylsiloxane-methylvinylsiloxane-methyl(3,3,3-trifluoropropyl)siloxane copolymer, terminal-blocked dimethylsiloxane-methylvinylsiloxane-methyl(3,3,3-trifluoropropyl)siloxane copolymer, terminal-blocked dimethylvinylsiloxane-methyl(3,3,3-trifluoropropyl)siloxane copolymer, terminal-blocked methyl(3,3,3-trifluoropropyl)siloxane-methylvinylsiloxane copolymer, terminal-blocked methyl(3,3,3-trifluoropropyl)siloxane-methylvinylsiloxane copolymer, and mixtures of two or more of these.
[0016] (B) Component has a BET specific surface area of 50 m2, as determined by the BET method using physical adsorption of an inert gas at low temperature and low humidity. 2 / g or more, and is a component that imparts excellent mechanical strength to the silicone rubber cured product obtained by curing the composition of the present invention. Examples of such silica powder include dry silica such as fumed silica, wet silica such as precipitated silica, and fine powder silica whose surface has been hydrophobized with an organosilicon compound such as organosilane, organosilazane, organopolysiloxane, diorganocyclopolysiloxane, etc. Also, these silicas may be blended in the form of a compound or masterbatch in which they are mixed in advance with the above-mentioned component (A) and, optionally, the plasticizer component (F). In practical terms, it is particularly preferable that component (B) is a silica powder whose surface has been hydrophobized.
[0017] The silica powder, which is component (B), has a BET specific surface area of 50 m as described above in order to improve the mechanical strength of the hardened product. 2 / g or more, and its BET specific surface area is 100m 2 The upper limit of the BET specific surface area of the silica powder is not particularly limited, but is, for example, 1000 m 2 / g or less, 2 / g or less.
[0018] If the amount of this component is too small, the mechanical strength after curing will be insufficient, and if the amount is too large, it will be difficult to incorporate it into component (A) and the handling and workability of the composition as a whole will decrease. Therefore, the amount of this component is in the range of 5 to 100 parts by mass, and particularly preferably 10 to 70 parts by mass, per 100 parts by mass of component (A).
[0019] The metal damage inhibitor of component (C) is one of the characteristic features of the present invention, and when used in combination with component (D), described below, it is possible to form a silicone rubber cured product with improved core wire adhesion prevention properties. On the other hand, even if the composition contains component (D), if component (C) is missing, the technical effects of the present invention cannot be achieved.
[0020] The metal inhibitor usable in the present invention may be one or more selected from known compounds such as diacylhydrazide compounds, oxalic acid compounds, aminotriazole compounds, etc. These metal inhibitors can be purchased from, for example, BASF or ADEKA. From the viewpoint of the technical effects of the present invention, it is preferable to use, as component (C), one or more metal inhibitors selected from diacylhydrazide compounds and aminotriazole compounds.
[0021] More specifically, the component (C) may be N,N'-diformylhydrazine, N,N'-diacetylhydrazine, N,N'-dipropionylhydrazine, N,N'-butyrylhydrazine, N-formyl-N'-acetylhydrazine, N,N'-dibenzoylhydrazine, N,N'-ditoluoylhydrazine, N,N'-disalicyloylhydrazine, N-formyl-N'-salicyloylhydrazine, N-formyl-N'-butyl-substituted hydrazine, Examples include salicyloylhydrazine, N-acetyl-N'-salicyloylhydrazine, N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl]hydrazine, di-(N-salicyloyl)hydrazine oxalate, di-(N-salicyloyl)hydrazine adipate, dodecandioyl-di-(N-salicyloyl)hydrazine, and 3-(N-salicyloyl)amino-1,2,4-triazole. Examples of commercially available products include the trade name "Irganox (registered trademark) MD-1024" (manufactured by BASF, N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl]hydrazine), the trade name "ADK STAB (registered trademark) CDA-6" (manufactured by ADEKA, dodecandioyl-di-(N-salicyloyl)hydrazine), and the trade name "ADK STAB CDA-1" (manufactured by ADEKA, 3-(N-salicyloyl)amino-1,2,4-triazole).
[0022] Here, the diacylhydrazide compound is represented by, for example, general formula (1). [ka] In the above general formula (1), R1 and R2 are the same or different and represent a hydrogen atom, a hydroxyl group, an alkyl group, a substituted alkyl group, an aryl group, a substituted aryl group such as a phenol group, an aralkyl group, or a substituted aralkyl group. R1 and R2 are preferably a monovalent hydrocarbon group containing an aryl group or a substituted aryl group such as a phenol group.
[0023] The aminotriazole compound is represented, for example, by the general formula (2). [ka] In the above general formula (2), R4 and R5 are the same or different and represent a hydrogen atom, an alkyl group, a substituted alkyl group, a substituted aryl group, a carboxyl group, an acyl group, an alkyl ester group, an allyl ester group, a halogen atom, or an alkali metal atom. In addition, in the above general formula (2), R3 represents a hydrogen atom or an acyl group. R4 and R5 are preferably acyl groups, and particularly preferably acyl groups having an aromatic ring such as a salicyloyl group or a benzoyl group.
[0024] The amount of the metal damage inhibitor (C) is 0.05 to 5 parts by mass, preferably 0.05 to 1.50 parts by mass, more preferably 0.05 to 1.00 parts by mass, and even more preferably 0.05 to 0.50 parts by mass, based on 100 parts by mass of the component (A). If the amount of the component (C) is less than the lower limit, the effect of improving the core wire adhesion prevention when the obtained silicone rubber cured product is used in a silicone rubber cured product covered electric wire may be insufficient. On the other hand, if the amount of the component (C) exceeds the upper limit, it is uneconomical, and especially if the component (C) is excessively mixed, the mechanical strength of the obtained silicone rubber cured product may decrease, or the silicone rubber cured product may become discolored, which may cause other problems.
[0025] The component (D) is one or more metal oxides selected from titanium oxide (D1) and magnesium oxide (D2), and the technical effects of the present invention are achieved by using a specific metal oxide, component (D), in combination with the component (C) in a certain quantitative range. On the other hand, even if other metal oxides (e.g., cerium oxide, iron oxide, zinc oxide, etc.) or fatty acid metal salts are used together with component (C) in place of component (D), the core wire adhesion prevention properties of the resulting silicone rubber cured product are not sufficiently improved. It is preferable that component (D) is a particulate metal oxide. Furthermore, at least a part of the component (D) according to the present invention may be titanium oxide (D1) from the viewpoint of the technical effects of the present invention, and this is preferable.
[0026] (D1) Titanium oxide is TiO 2(titanium dioxide) and may have any of three types of crystal forms, i.e., anatase type (anatase), rutile type (rutile), and brookite type (brookite). Of the above, anatase type and rutile type titanium oxide are used on an industrial scale, and anatase type and rutile type titanium oxide can be preferably used in the present invention. In addition, as component (D1) of the present invention, a mixture of two or more types of titanium oxide having different crystal forms may be used. In addition, titanium oxide as component (D1) is preferably in the form of fine particles, and although there is no particular restriction on the average primary particle size, those having an average primary particle size of 5 to 200 nm, 5 to 100 nm are industrially preferred.
[0027] The titanium oxide fine particles that can be used in the present invention are not particularly limited in terms of their specific surface area, but the BET specific surface area determined by the BET method using physical adsorption of an inert gas at low temperature and low humidity is preferably 10 m 2 / g or more, more preferably 15m 2 / g or more, more preferably 30m 2 / g or more, and the BET specific surface area is preferably 500 m 2 / g or less, more preferably 300m 2 / g or less, more preferably 200m 2 In the present invention, the titanium oxide that is practically suitable is 10 to 200 m 2 / g BET specific surface area.
[0028] The shape of the (D2) magnesium oxide (MgO) is not particularly limited, and may be, for example, a bulk or particulate shape, but particulate shape is preferred. Particulate shape here may include not only a perfect sphere but also an approximately spherical shape. The average particle size of the magnesium oxide particles is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less, and particularly preferably 4 μm or less. The lower limit of the average particle size of the particulate magnesium compound is not particularly limited, but is preferably 1 nm or more, more preferably 10 nm or more, even more preferably 100 nm or more, and particularly preferably 500 nm or more. In the present invention, magnesium oxide particles suitable for practical use have an average particle size of 0.5 to 10 μm.
[0029] The amount of the (D) component, as the total amount of the (D1) and (D2) components, is in the range of 0.1 to 10 parts by mass, preferably 0.5 to 7.5 parts by mass, and more preferably 0.5 to 5.0 parts by mass, per 100 parts by mass of the (A) component. If the amount of the (D) component is less than the lower limit, the effect of improving the core wire adhesion prevention when the obtained silicone rubber cured product is used in a silicone rubber-coated electric wire may be insufficient. On the other hand, if the amount of the (D) component is more than the upper limit, it is uneconomical, and especially if the (D) component is excessively mixed, the physical / mechanical strength of the obtained silicone rubber cured product may decrease.
[0030] In the present invention, when the component (D) is blended in the composition, it is particularly preferred that each of the titanium oxide (D1) and the magnesium oxide (D2) is premixed with an organopolysiloxane such as the component (A) to form a masterbatch containing the component (D), which is then mixed with the other components. The organopolysiloxane used to prepare the masterbatch containing the component (D) may be, and is preferably, the same organopolysiloxane as the above-mentioned component (A).
[0031] Component (E) is a curing agent for the curable silicone composition of the present invention, specifically, one or more curing agents selected from (E1) addition reaction curing agents and (E2) organic peroxides. These can be any curing agent known in the art that can be used without restriction as a curing agent for the organopolysiloxane having an alkenyl group, component (A). By using component (E), the curable silicone composition of the present invention is particularly heat curable. In the present composition, the amount of the curing agent (E) component is not particularly limited as long as it is an amount necessary for curing the present composition. The amount of the (E) component can be appropriately set depending on its type as described later, but can be, for example, within the range of 0.05 to 10 parts by mass, 0.10 to 5 parts by mass, or 0.50 to 2.5 parts by mass per 100 parts by mass of the (A) component.
[0032] The (E1) addition reaction curing agent is, for example, a combination of the (E1-1) organohydrogenpolysiloxane, which is a crosslinking agent, and the (E1-2) hydrosilylation reaction catalyst. Specifically, in the presence of the (E1-2) component, the (A) component undergoes a crosslinking reaction with the (E1-1) component, thereby causing the curing reaction to proceed, and the composition according to the present invention forms a silicone rubber cured product.
[0033] More specifically, the organohydrogenpolysiloxane (E1-1) is a crosslinking agent for the silicone rubber composition of the present invention, and in the presence of the hydrosilylation catalyst (E1-2), the silicon-bonded hydrogen atoms in the organohydrogenpolysiloxane (E1-1) undergo an addition reaction with the silicon-bonded alkenyl groups in the component (A) to crosslink and cure. The organohydrogenpolysiloxane has at least two silicon-bonded hydrogen atoms in one molecule. Examples of organic groups other than the silicon-bonded hydrogen atoms include alkyl groups such as methyl, ethyl, and propyl groups; aryl groups such as phenyl and tolyl groups; and halogen-substituted alkyl groups such as 3,3,3-trifluoropropyl and 3-chloropropyl groups. The molecular structure of the organohydrogenpolysiloxane may be linear, branched linear, cyclic, or network, and two or more types of organohydrogenpolysiloxanes may be used in combination.
[0034] The molecular weight of the organohydrogenpolysiloxane is not particularly limited, but the viscosity at 25°C is preferably in the range of 3 to 10,000 mPa·s. When the present composition is cured by an addition reaction, the content of the organohydrogenpolysiloxane is preferably in the range where the ratio of the amount of substance (number of moles) of silicon-bonded hydrogen atoms in component (E1-1) to 1 mole of silicon-bonded alkenyl groups in component (A) is 0.5 to 20, and more preferably in the range of 0.1.0 to 3.0. If the content of silicon-bonded hydrogen atoms in component (E1-1) in the present composition is equal to or greater than the lower limit, the curable silicone composition can be sufficiently cured. On the other hand, if the content of silicon-bonded hydrogen atoms in component (E1-1) in the present composition is equal to or less than the upper limit, the excessive generation of hydrogen as a by-product can be prevented, and foaming of the obtained silicone rubber cured product can be suppressed.
[0035] The hydrosilylation catalyst (E1-2) is a component that catalyzes the crosslinking reaction between the component (A) and the component (E1-1). The hydrosilylation catalyst includes, for example, a platinum catalyst, a rhodium catalyst, and / or a palladium catalyst, and is preferably a platinum catalyst because it can significantly accelerate curing. The platinum catalyst may be, for example, platinum fine powder, chloroplatinic acid, an alcohol solution of chloroplatinic acid, a platinum-alkenylsiloxane complex, a platinum-olefin complex, a platinum-carbonyl complex, or a catalyst in which these platinum catalysts are dispersed or encapsulated in a thermoplastic resin such as a silicone resin, a polycarbonate resin, or an acrylic resin. Among these, a platinum-alkenylsiloxane complex is preferred. The alkenylsiloxane may be 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, 1,1,3,3-tetravinyldimethyldisiloxane, dimethylvinylsiloxy group-blocked methyl(3,3,3-trifluoropropyl)siloxane oligomer, alkenylsiloxanes in which a portion of the methyl groups of these alkenylsiloxanes have been substituted with ethyl groups, phenyl groups, or the like, or alkenylsiloxanes in which the vinyl groups of these alkenylsiloxanes have been substituted with allyl groups, hexenyl groups, or the like. In particular, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred because the platinum-alkenylsiloxane complex has good stability. Other catalysts for promoting the hydrosilylation reaction include non-platinum metal catalysts such as iron, ruthenium, and iron / cobalt. Furthermore, in one embodiment of the present invention, a hydrosilylation reaction catalyst such as a photoactive platinum complex curing catalyst that promotes the hydrosilylation reaction by irradiation with high-energy rays such as ultraviolet rays other than heating may be used. The hydrosilylation reaction catalyst may be a β-diketone platinum complex or a platinum complex having a cyclic diene compound as a ligand.
[0036] The content of the hydrosilylation catalyst is a catalytic amount that accelerates the curing of the present composition, and when the present composition is cured by an addition reaction, the amount of metal atoms in the hydrosilylation catalyst may be within the range of 0.1 to 1,000 ppm, 0.1 to 500 ppm, or 0.1 to 250 ppm by mass relative to the total solid content (components that form a cured product) of the present composition. If the content of the hydrosilylation catalyst is equal to or greater than the lower limit, the curing reaction of the present composition is sufficiently accelerated. On the other hand, if the content of the hydrosilylation catalyst is equal to or less than the upper limit, the obtained silicone rubber cured product does not suffer from problems such as coloration due to the catalyst metal.
[0037] The composition of the present invention may and preferably uses an organic peroxide (E2) as a part or the whole of the curing agent (E). The organic peroxide may be an alkyl peroxide, a diacyl peroxide, an ester peroxide, or a carbonate peroxide, and the type is not particularly limited, but it is preferable that the temperature at which the half-life is 10 hours is 70°C or higher, and the temperature may be 90°C or higher or 95°C or higher. By using the component (E2), the entire composition including the component (A) can be thermally cured without using a crosslinking agent or the like.
[0038] Specific examples of organic peroxides include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, p-methylbenzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dicumyl peroxide, 2,5-dimethyl-bis(2,5-t-butylperoxy)hexane, di-t-butyl peroxide, t-butyl perbenzoate, etc. These may be used alone or in combination of two or more.
[0039] In the present composition, the content of the organic peroxide is not particularly limited, but in practical terms, it is preferably within the range of 0.05 to 10 parts by mass, more preferably within the range of 0.10 to 5.0 parts by mass, and even more preferably within the range of 0.50 to 2.5 parts by mass, when the component (A) is 100 parts by mass. In addition, the present composition contains silica powder as the component (B), and from the viewpoint of improving the curing reactivity and the mechanical strength of the obtained silicone rubber cured product, it is preferable that the curing agent (E) is an organic peroxide (E2). In other words, the present composition is preferably a peroxide curing reactive composition.
[0040] The present composition is preferably heat-curable by using component (E), and can form a silicone rubber cured product by carrying out a heat curing reaction at a temperature above room temperature, preferably above 60°C. In particular, when the curing reaction is a peroxide curing reaction, the curing reactive group in component (A) is a functional group that is radically reactive with peroxide, and peroxide curing reactive functional groups such as alkyl groups, alkenyl groups, acrylic groups, and hydroxyl groups can be used without restriction. Note that, since a peroxide curing reaction generally proceeds at a high temperature of 150°C or higher, it is particularly preferable to carry out the curing reaction at a temperature of 150°C or higher.
[0041] In the present invention, in order to cover an electric conductor such as an electric wire with a silicone rubber cured product and obtain a silicone rubber cured product covered electric wire with improved core wire adhesion prevention properties, it is particularly preferable to carry out the curing reaction at a high temperature of 150 to 600° C., 150 to 500° C., or 150 to 450° C. In the case of an addition curing reaction, a low-temperature heat curing reaction of 100° C. or less, 80° C. or less, or 70° C. or less can also be selected. When the curing reaction is a hydrosilylation curing reaction, high-energy radiation using a photoactive platinum complex curing catalyst or the like may be carried out.
[0042] The composition of the present invention preferably contains, as a plasticizer, (F) a diorganopolysiloxane having silanol groups at both molecular chain terminals (diorganopolysiloxane capped with silanol groups at both molecular chain terminals) selected from siloxane oligomers such as α,ω-silanol group-capped dimethylsiloxane oligomer, α,ω-silanol group-capped methylphenylsiloxane oligomer, α,ω-silanol group-capped methylvinylsiloxane oligomer, α,ω-silanol group-capped dimethylsiloxane-methylvinylsiloxane copolymer oligomer, etc. The diorganopolysiloxane of component (F) preferably has a viscosity at 25°C of 1 to 1,000 mPa s. The diorganopolysiloxane serving as component (F) may be one or a combination of two or more diorganopolysiloxanes having a viscosity at 25° C. in the range of preferably 10 to 200 mPa·s, and more preferably 10 to 100 mPa·s. This component is particularly preferably blended in the present composition in the form of a compound or masterbatch in which it is premixed with the aforementioned components (A) and (B), and the amount used is preferably within the range of 0.05 to 50 parts by mass, more preferably within the range of 0.05 to 20 parts by mass, even more preferably within the range of 0.50 to 10 parts by mass, and particularly preferably within the range of 1.00 to 7 parts by mass, based on 100 parts by mass of component (A).
[0043] When the composition cures by an addition reaction, in order to adjust the curing speed, working pot life, and pot life, it may contain a curing retarder (G) in addition to the addition reaction curing agent (E1). When the hydrosilylation reaction catalyst (E1-2) is a capsule type or a photoactive platinum complex, it is possible to design a composition that has a practically sufficient curing speed, working pot life, and pot life even if the amount of component (G) used is small or is substantially absent.
[0044] (G) Examples of the hardening retarder include alkyne alcohols such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynyl-1-cyclohexanol, 2-ethynylisopropanol, and 2-ethynylbutan-2-ol; silylated acetylene alcohols such as trimethyl(3,5-dimethyl-1-hexyn-3-oxy)silane, dimethylbis(3-methyl-1-butynoxy)silane, methylvinylbis(3-methyl-1-butyn-3-oxy)silane, and [(1,1-dimethyl-2-propynyl)oxy]trimethylsilane; 2-isobutyl-1-buten-3-yne, 3,5-dimethyl-3-hexen-1-yne, 3-methyl-3-penten-1-yne, 3-methyl-3 3-hexen-1-yne, 1-ethynylcyclohexene, 3-ethyl-3-buten-1-yne, 3-phenyl-3-buten-1-yne, and the like, and ene-yne compounds; unsaturated carboxylic acid esters such as diallyl maleate, dimethyl maleate, diethyl fumarate, diallyl fumarate, bis-2-methoxy-1-methylethyl maleate, monooctyl maleate, monoisooctyl maleate, monoallyl maleate, monomethyl maleate, monoethyl fumarate, monoallyl fumarate, and 2-methoxy-1-methylethyl maleate; alkenyl siloxanes such as 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane; and benzotriazole. These may be used alone or in combination of two or more.
[0045] The amount of the cure retarder may be appropriately selected depending on the method of use, molding method, etc. of the present composition. The amount generally used is in the range of 0.001 to 5 mass % based on the total mass of the addition reaction curable silicone composition (the present composition).
[0046] In addition, the composition may be blended with various other additives that are generally used in curable silicone compositions, provided that the objectives of the present invention are not impaired.Examples of such additives include diatomaceous earth, quartz powder, calcium carbonate, and other extender fillers; alumina, zinc oxide, boron nitride, and other thermal conductivity improvers; magnesium hydroxide, aluminum hydroxide, and other flame retardant improvers; acetylene black, furnace black, channel black, and other carbon blacks; red iron oxide, and other pigments; rare earth oxides, cerium silanolate, cerium fatty acid salts, and other heat resistance improvers; stearic acid, zinc stearate, calcium stearate, and other fatty acids and their metal salts, and other mold release agents; and alkoxysilane, diphenylsilanediol, carbon functional silane, and non-functional silicone oil, and other dispersants.
[0047] The silicone composition of the present invention can be obtained by uniformly mixing the above-mentioned components using a rubber mixer such as a two-roll mill, a Banbury mixer, a kneader mixer, etc. There are no particular limitations on the mixing order, temperature conditions, time, etc., and any method known in the art may be used.
[0048] The method for curing the present composition is not limited, and can be mold molding, compression molding, transfer molding, injection molding, extrusion molding, calendar molding, etc. The curing method is also not limited, and can be selected from well-known curing methods such as steam vulcanization and hot air vulcanization.
[0049] When this composition is applied to a core wire, which is an electrical conductor, it is molded, for example, at 100 to 450°C for a few seconds to an hour under pressure or without pressure, to obtain a silicone rubber cured product coated electric wire in which adhesion to the core wire is prevented (i.e., excellent core wire adhesion prevention properties).
[0050] In other words, the silicone rubber-cured covered electric wire obtained in this manner can fully prevent adhesion to the core wire even if it is subjected to secondary vulcanization under harsh conditions, such as four hours at 220°C, or even if a silicone-based, polyester-based varnish or the like is heat-treated on the covered electric wire.
[0051] Furthermore, a silicone rubber cured product covered electric wire having a structure in which a core wire is covered with a silicone rubber cured product can be obtained by a method for producing a silicone rubber cured product covered electric wire, which includes the steps of applying the curable silicone composition onto a core wire and curing the composition by the method described above. EXAMPLES
[0052] The curable silicone composition of the present invention will be described in more detail with reference to examples and comparative examples. The present invention is not limited to these examples. In the examples, the properties such as viscosity and Williams plasticity are values at room temperature (25°C) unless otherwise specified. The viscosity (mPa·s) is a value measured using a rotational viscometer conforming to JIS K7117-1. In addition, the Williams plasticity is a value measured according to the method specified in JIS K6249. The physical properties and core wire adhesion prevention properties of the silicone rubber cured product obtained from the curable silicone composition were measured and evaluated as follows.
[0053] <Physical properties of cured silicone rubber> Each curable silicone composition was compression molded under heating conditions of 120°C for 10 minutes to obtain a 2mm thick silicone rubber sheet as a silicone rubber cured product. The hardness, tensile strength (unit: MPa), elongation (unit: %), and tear strength (angle, unit: N / mm) of the sheet were measured according to the method of JIS K 6249:2003. The results are shown in Tables 1 and 2.
[0054] Separately, the physical properties of the cured product after heat resistance were also measured, and used as a method for evaluating heat resistance. First, each curable silicone composition was compression molded under heating conditions of 120°C x 10 minutes to obtain a silicone rubber sheet with a thickness of 2 mm as a silicone rubber cured product. The sheet was placed in an environment of 220°C for 96 hours, and then the hardness, tensile strength (unit: MPa), and elongation (unit: %) were measured according to a method in accordance with JIS K 6249:2003. The results are shown in Tables 1 and 2.
[0055] <Core wire adhesion prevention properties of cured silicone rubber> -Evaluation experiment 1 (secondary vulcanization: 200℃ / 4 hours)- Each curable silicone composition was coated on a tin-plated annealed copper wire of 7 strands, each 30 cm long and 0.26 mm in diameter, to a thickness of 1.5 mm, and compression molded under heating conditions of 120°C x 10 minutes to obtain a coated body. The obtained coated body was subjected to secondary vulcanization (secondary heat treatment) in an oven at 200°C for 4 hours, and then left at room temperature for at least one day to obtain a silicone rubber cured product coated electric wire. The silicone rubber cured product of this silicone rubber cured product coated electric wire was peeled off from the core wire using a wire stripper, and visually inspected to see if the silicone rubber cured product remained on the core wire. The judgment was made based on past experience and evaluated in three stages of core wire adhesion prevention, namely, those that clearly cause problems when soldering (C rating), those that can be used with some difficulty (B rating), and those that can be used without problems (A rating). The results are shown in Tables 1 and 2. -Evaluation experiment 2 (secondary vulcanization: 220℃ / 4 hours)- A coating was prepared in the same manner as in Evaluation Experiment 1. The obtained coating was subjected to secondary vulcanization (secondary heat treatment) in an oven at 220°C for 4 hours and then left at room temperature for at least one day to obtain a silicone rubber cured product coated electric wire. The silicone rubber cured product coated electric wire was evaluated for its ability to prevent adhesion of the core wire in the same manner as in Evaluation Experiment 1. The results are shown in Tables 1 and 2.
[0056] <Preparation example: Silicone rubber-based compound> As the component (A), 70 parts by mass of (a-1) dimethylsiloxane-methylvinylsiloxane copolymer terminated at both molecular chain ends by dimethylvinylsiloxy groups (raw rubber-like, vinyl group content: 0.064% by mass, weight-average molecular weight: about 700,000, Williams plasticity: 160) and 30 parts by mass of (a-2) dimethylsiloxane-methylvinylsiloxane copolymer terminated at both molecular chain ends by dimethylvinylsiloxy groups (raw rubber-like, vinyl group content: 0.212% by mass, weight-average molecular weight: about 700,000, Williams plasticity: 160) were used, and (b-1) dried process silica fine powder (BET specific surface area: 130 m) was used as the component (B). 240 parts by mass of (A) component (Ag / g), 4 parts by mass of (f-1) α,ω-silanol group-blocked dimethylsiloxane oligomer (viscosity: 40 mPa s) and 0.8 parts by mass of (f-2) α,ω-silanol group-blocked dimethylsiloxane-methylvinylsiloxane copolymer oligomer (viscosity: 20 mPa s) as component (F) (plasticizer) were charged into a kneader mixer and the mixture was kneaded uniformly. The mixture was then kneaded at 175°C for 90 minutes to prepare a silicone rubber base compound containing components (A), (B) and (F).
[0057] The following component was used as the metal damage inhibitor (C). (c-1): 3-(N-salicyloyl)amino-1,2,4-triazole (manufactured by ADEKA Corporation, trade name "ADEKA STAB CDA-1") (c-2): Dodecane dioyl-di-(N-salicyloyl)hydrazine (manufactured by ADEKA Corporation, product name "ADEKA STAB CDA-6") (c-3): N,N'-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl]hydrazine (manufactured by BASF, trade name "Irganox MD-1024")
[0058] The following components were used as titanium oxide and magnesium oxide in component (D). (d-1): Titanium oxide masterbatch Titanium oxide (manufactured by Nippon Aerosil Co., Ltd., trade name "P-25", BET specific surface area: 50 m 2 46 parts by mass of titanium dioxide (100% by mass, 100% by mass of dimethylsiloxane / methylvinylsiloxane copolymer (99.8 mol % dimethylsiloxane unit and 0.13 mol % methylvinylsiloxane unit) capped at both ends with dimethylvinylsiloxy groups (raw rubber-like, degree of polymerization: 6,000, Williams plasticity: 160, corresponds to component (A)) were mixed using a two-roll mill to prepare (d-1) titanium dioxide master batch. The proportion of titanium dioxide in this master batch was 46% by mass. (d-2): Magnesium oxide masterbatch 20 parts by mass of magnesium oxide (Kyowa Chemical Industry Co., Ltd., average particle size: 3.1 μm) and 80 parts by mass of dimethylsiloxane-methylvinylsiloxane copolymer capped with dimethylvinylsiloxy groups at both ends of the molecular chain containing 99.8 mol % dimethylsiloxane units and 0.13 mol % methylvinylsiloxane units (raw rubber-like, degree of polymerization 6,000, Williams plasticity: 160, corresponding to component (A)) were mixed using a two-roll mill to prepare (d-2) magnesium oxide master batch. The proportion of magnesium oxide contained in this master batch was 20% by mass.
[0059] For comparative experiments, the following ingredients were used: (Cerium oxide masterbatch) A cerium oxide master batch was prepared by mixing 43 parts by mass of cerium oxide powder (manufactured by Nikki KK, product name "High Purity Cerium Oxide") and 57 parts by mass of dimethylsiloxane-methylvinylsiloxane copolymer capped at both molecular chain ends with dimethylvinylsiloxy groups, containing 99.8 mol % dimethylsiloxane units and 0.13 mol % methylvinylsiloxane units (raw rubber-like, degree of polymerization: 6,000, Williams plasticity: 160, corresponding to component (A)) using a two-roll mill. The proportion of cerium oxide in this master batch was 43% by mass. (Iron oxide masterbatch) An iron oxide master batch was prepared by mixing 50 parts by mass of iron trioxide (average particle size: 0.09 μm) and 50 parts by mass of dimethylsiloxane-methylvinylsiloxane copolymer (raw rubber-like, degree of polymerization: 6,000, Williams plasticity: 160, corresponding to component (A)) containing 99.8 mol % dimethylsiloxane unit and 0.13 mol % methylvinylsiloxane unit and terminated with dimethylvinylsiloxy group at both molecular chain ends using a two-roll mill. The proportion of iron oxide contained in this master batch was 50% by mass. (Zinc oxide masterbatch) A zinc oxide master batch was prepared by mixing 50 parts by mass of zinc oxide No. 1 with 50 parts by mass of a dimethylsiloxane-methylvinylsiloxane copolymer (raw rubber-like, degree of polymerization 6,000, Williams plasticity: 160, component (A)) containing 99.8 mol% dimethylsiloxane units and 0.13 mol% methylvinylsiloxane units and terminated at both molecular chain ends with dimethylvinylsiloxy groups using a two-roll mill. The proportion of zinc oxide in this master batch was 50% by mass. (Zinc stearate masterbatch) A zinc stearate masterbatch was prepared by mixing 50 parts by mass of zinc stearate and 50 parts by mass of dimethylsiloxane-methylvinylsiloxane copolymer (raw rubber-like, degree of polymerization: 6,000, Williams plasticity: 160, component (A)) capped at both ends of the molecular chain with dimethylvinylsiloxy groups, containing 99.8 mol% dimethylsiloxane units and 0.13 mol% methylvinylsiloxane units, using a two-roll mill. The proportion of zinc stearate in this masterbatch was 50% by mass. (Amino group-containing triazine compounds) A mixture containing 2,4,6-triamino-1,3,5-triazine as a main component (manufactured by ADEKA Corporation, product name: "ADEKA STAB ZS-27") was prepared. (Triallyl isocyanurate) Triallyl isocyanurate (TAIC) was prepared. (Benzotriazole masterbatch) A benzotriazole master batch was prepared by mixing 25 parts by mass of benzotriazole with 75 parts by mass of a dimethylsiloxane-methylvinylsiloxane copolymer (raw rubber-like, degree of polymerization 6,000, Williams plasticity: 160, component (A)) containing 99.8 mol % dimethylsiloxane units and 0.13 mol % methylvinylsiloxane units and terminated at both molecular chain ends with dimethylvinylsiloxy groups using a two-roll mill. The proportion of benzotriazole in this master batch was 25% by mass.
[0060] The following component was used as the hardener for component (E). <(E1) Addition reaction curing agent> (e-1): Crosslinking agent (E1-1) A dimethylsiloxane-methylhydrogensiloxane copolymer with both ends blocked by trimethylsiloxy groups (viscosity: 15 mPa·s, silicon-bonded hydrogen atom content: approximately 0.8% by mass) was used. (e-2): Hydrosilylation reaction catalyst (E1-2) A 1,3-divinyltetramethyldisiloxane solution of a platinum complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane (platinum metal content = approximately 6,700 ppm by mass) was prepared. <(E2)Organic peroxide> (e-3): Peroxide masterbatch A peroxide masterbatch consisting of 50 mass % p-methylbenzoyl peroxide ((E2) organic peroxide) and 50 mass % silicone oil (liquid dimethylpolysiloxane) was prepared.
[0061] As the hardening retarder of the component (G), (g-1): 1-ethynyl-1-cyclohexanol was prepared.
[0062] <Examples 1 to 9 and Comparative Examples 1 to 10> Curable silicone compositions were prepared by mixing the above prepared materials (silicone rubber base compound, various compounds, and various masterbatches) so that the blending ratios of the various components were as shown in Table 1 or Table 2. The obtained curable silicone composition was used to carry out the various evaluations described above.
[0063] In the following Tables 1 and 2, The "titanium oxide master batch" corresponding to "(d-1)" contains 46% by mass of titanium oxide, which is the component (D), and 54% by mass of the component (A), The "magnesium oxide master batch" corresponding to "(d-2)" contains 20% by mass of magnesium oxide, which is the component (D), and 80% by mass of the component (A), The "cerium oxide master batch" contains 43% by mass of cerium oxide and 57% by mass of component (A), The "iron oxide masterbatch" contains 50% by mass of iron oxide and 50% by mass of component (A), The "zinc oxide masterbatch" contains 50% by mass of zinc oxide and 50% by mass of component (A), "Zinc stearate masterbatch" contains 50% by mass of zinc stearate and 50% by mass of component (A), The "benzotriazole master batch" contains 25% by mass of benzotriazole and 25% by mass of component (A), and The "peroxide master batch" corresponding to "(e-3)" contains 50 mass% of p-methylbenzoyl peroxide, which is the component (E2). In addition, in the following Tables 1 and 2, "ZS-27" means a mixture containing 2,4,6-triamino-1,3,5-triazine as the main component; "TAIC" means triallyl isocyanurate.
[0064] [Table 1]
[0065] [Table 2]
[0066] It can be seen from Table 1 that by using a curable silicone composition containing components (A) to (E) in the specified ranges, it is possible to form a silicone rubber cured product that has excellent core wire adhesion prevention properties. On the other hand, Table 2 shows that in Comparative Examples 1 and 7 to 10, which used a curable silicone composition not containing component (C), Comparative Examples 2, 3, 5 and 6, which used a curable silicone composition not containing component (D), and Comparative Example 4, which used a curable silicone composition that contained component (C) but in an amount outside the specified range, the core wire adhesion prevention properties of the silicone rubber cured product were reduced compared to the Examples. [Industrial Applicability]
[0067] The silicone rubber cured product obtained by curing the curable silicone composition of the present invention has improved core wire adhesion prevention properties and is therefore useful for coating electric conductors such as electric wires, and is particularly suitable for silicone rubber cured product coated electric wire applications, and is useful as a material for silicone rubber cured product coated electric wires. Furthermore, the silicone rubber cured product obtained by curing the curable silicone composition of the present invention has heat resistance and electrical insulation resistance sufficient for practical use.
Claims
1. (A) organopolysiloxane having at least two alkenyl groups in one molecule: 100 parts by mass, (B) BET specific surface area is 50 m 2 / g or more: 5 to 100 parts by mass of silica powder, (C) Metal damage inhibitor: 0.05 to 5 parts by mass (D) One or more metal oxides selected from (D1) titanium oxide and (D2) magnesium oxide: 0.1 to 10 parts by mass (E) One or more curing agents selected from (E1) an addition reaction curing agent and (E2) an organic peroxide: an amount necessary for curing the present composition 1. A curable silicone composition comprising:
2. 2. The curable silicone composition according to claim 1, wherein component (C) is one or more compounds selected from the group consisting of (C1) diacylhydrazide compounds and (C2) aminotriazole compounds.
3. 2. The curable silicone composition according to claim 1, wherein component (D) comprises (D1) titanium oxide.
4. The curable silicone composition according to claim 1 , wherein component (E) comprises (E2) an organic peroxide.
5. 2. The curable silicone composition according to claim 1, wherein component (A) is a raw rubber-like organopolysiloxane having a Williams plasticity in the range of 100 to 800, as measured in accordance with the method specified in JIS K6249.
6. 2. The curable silicone composition according to claim 1, further comprising: (F) 0.05 to 50 parts by mass of a diorganopolysiloxane capped at both molecular chain terminals with silanol groups and having a viscosity at 25° C. of 1 to 1,000 mPa·s.
7. A cured silicone rubber product obtained by curing the curable silicone composition according to any one of claims 1 to 6.
8. A silicone rubber cured product-covered electric wire, comprising a core wire covered with the silicone rubber cured product according to claim 7.
9. A method for producing a silicone rubber cured product-covered electric wire, comprising the steps of applying the curable silicone composition according to any one of claims 1 to 6 onto a core wire and curing the composition.
Citation Information
Patent Citations
Three-wheel drive vehicle for traveling on rough ground
JP1987026124A
Two-pack curing type silicone composition
JP2006056986A
Addition curing type rubber composition and molded article thereof
JP2008163122A
Silicone composition, silicone rubber cured product, and power cable
JP2019077735A